Performance académico y su relación con el acceso al empleo en áreas contables en estudiantes de contabilidad de la Universidad Nacional de la Amazonía Peruana año 2024 - Padilla Sinarahua, Huber Alfredo (2025)
The study analyzed the relationship between the academic performance of accounting students and their access to jobs in accounting areas in the city of Iquitos in 2024, with a quantitative approach, a non-experimental design and a study population of 75 accounting students, for which a data collection instrument with 30 items and a statistical reliability in Cronbach's alpha of 0.931 was applied, the results revealed that there is a positive and significant moderate relationship between academic performance and access to jobs, showing that students with better grades have greater job opportunities in the accounting sector, in terms of soft skills, a moderate relationship with employability was identified, highlighting that competencies such as effective communication, teamwork and professional ethics are valued, that complementary training, such as specialized certifications and additional courses, also presented a significant relationship with job insertion, the descriptive analysis shows that 87% of students demonstrate good performance in solving accounting problems, while 11% of students have a high level of employment. 75% use specialized digital tools and 88% act according to ethical principles. Access to employment remains a challenge, as only 33% perceive sufficient job opportunities, while 51% consider lack of experience to be a significant barrier.